(untitled) (International Journal of Engineering and Computer Science, 2016)
The tourism industry of a country is important to its economy and is ever expanding. It is a very diverse industry that accommodates even very particular interests. Like any other industry, it has its fair share of online representations of the real world at present. However, there isn’t sufficient intelligence in these very static systems. "Smart-tourism" is something that must be further explored. There is so much potential in both, the information available online and in the tourism industry, waiting to be harnessed. A combination of the two along with a recommendation engine will give it all, a much needed, human touch.